FAKTOR YANG BERPENGARUH PADA PRODUKTIVITAS PEKERJAAN TANAH DENGAN METODE SPSS - Billing Billing; Baso Mursidi; Fitriah Mas'ud (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2017)
Abstract Human resources is one of the factors thatinflueence in a job, what if it is not backed up with human resources both in terms of quality and productivity will not provide maximum results, and it can be concluded that worker productlvlry is the ability of a worker in production compared with inputs used, a worker can be said to be productive if it is able to produce goods or services as expected in a short time or right. The purpose of this study is to determine the level of productivity of workers and to determine the influence of the worker’s age,work experience, field conditions ( weather) health workers and heavy equipment used on the level of prodiktivitas labor on the project increased roads lansilowo- tumburano with observing the 24 labor and is accompanied by filling the questionnaire.